2017
DOI: 10.1155/2017/9456020
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between the Androgen Receptor and PPAR Gamma Signaling Pathways in the Prostate

Abstract: Nuclear receptors are a superfamily of ligand-activated transcription factors that play critical roles in the regulation of normal biological processes and several disease states. Of the nuclear receptors expressed within the prostate, the androgen receptor (AR) promotes the differentiation of prostatic epithelial cells and stimulates production of enzymes needed for liquefaction of semen. Multiple forms of AR also promote the growth of both early and late stage prostate cancers. As a result, drugs that target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 134 publications
(143 reference statements)
0
18
0
Order By: Relevance
“…The TF XBP1, mediating cellular stress responses, is proposed as a predictor marker for PCa [ 34 ]. The bidirectional crosstalk between PPARG and AR regulates growth and development both in normal and in tumor prostate, as recently highlighted [ 35 ]. Using Cytoscape, we generated a network visualization of the predicted regulatory interaction between hK-TFs and 51 DIhKPs ( Figure S4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TF XBP1, mediating cellular stress responses, is proposed as a predictor marker for PCa [ 34 ]. The bidirectional crosstalk between PPARG and AR regulates growth and development both in normal and in tumor prostate, as recently highlighted [ 35 ]. Using Cytoscape, we generated a network visualization of the predicted regulatory interaction between hK-TFs and 51 DIhKPs ( Figure S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the six hK-TFs, AR-controlled PPARG and HOX13 can be associated to ADT resistance. A recent study [ 35 ] has reported that PPARG controls prostate cell growth and differentiation and is involved in androgen-dependent PCa and CRPC evolution, acting as a tumor suppressor through its interplay with AR. The TF HOXA13, whose expression is associated with unfavorable survival [ 32 ], and the HOXB13, which controls PCa cell growth by inhibiting AR signaling [ 31 ], are also involved in PCa evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term responses at PSA levels <0.1 ng/ml occurred in rapidly progressive prostate cancer with PSA doubling times <3 months using combined transcriptional modulation, dexamethasone and pioglitazone in addition to metronomic low-dose chemotherapy. Pioglitazone may activate PPARγ, which is suggested to be a tumor suppressor in prostate cancer (Olokpa et al, 2017 ). The addition of imatinib in this schedule did not add any benefit.…”
Section: Master Modulators the Backbone Of Anakoinosis Inducing Thermentioning
confidence: 99%
“…In fact, multiple NRs are expressed in the normal prostate and are disrupted in PCa. NR actions are integrated by shared genomic binding regions, shared co-factors and the coregulation of ligand availability 61 . Non-coding RNAs including miRNA and lncRNA target NRs, their co-factors and target genes to also exert control of signaling 74,77 .…”
Section: Introductionmentioning
confidence: 99%